Network positions and efforts to innovate in a small Canadian optics and photonics clusters. (22nd March 2007) - Ouimet, Mathieu; Landry, Rejean; Amara, Nabil
This paper explores the association between the network positions of firms within a small optics and photonics cluster and their efforts to innovate. Our emphasis in this paper differs from much of the previous work on clusters in that we adopt a systematic social network analysis approach that allows us to construct network indicators measuring the network positions of firms within the Quebec optics and photonics cluster. The following three network measures are used in this paper: degree, betweenness and effective size. These network measures are used to assess whether or not network positions matter with regard to efforts to innovate within a small high-tech cluster. The results showed that participating firms were all highly innovative and highly connected to a large variety of organisations.